Fundamentals of crystallography and mineralogy study aid - Yakich, T. Yu. geologist Associate Professor of Tomsk Polytechnic University, Candidate of geological and mineralogical sciences 1984- (Tomsk Polytechnic University Publishing House, 2022)
The manual outlines the terms, concepts, basic principles and laws of crystallography, the mechanisms for describing the symmetry of crystals, the algorithm for determining and forming the names of simple shapes. Л general idea of the origin, growth of crystals and processes of mineral formation is given. The main physical and morphological properties of minerals are considered. Descriptive mineralogy includes a list of about 100 of the most common minerals. The manual is intended for students-geologists studying in the direction of 21.05.02 specialty "Applied Geology".